Increasing the Capacity of Midwives in Managing Diastasis Recti Abdominalis in Postpartum Care Based on Evidence-Based Practice - Lasiyati Yuswo Yani (Kirana Publisher (KNPub), 2026)
Diastasis Recti Abdominalis (DRA) is a postpartum musculoskeletal problem that is often overlooked, even though it poses a risk of reducing the quality of life of postpartum mothers. Midwives as the frontline of postpartum care need to have the capacity to detect and provide safe initial management. This Community Service (PKM) activity aims to improve midwives' knowledge and clinical skills in DRA management through structured Postnatal Yoga technique training. The service partner is the Indonesian Midwives Association (IBI) Branch X which involves 30 independent practicing midwives. The implementation method uses interactive lectures, manual detection demonstrations, and postpartum yoga movement modification workshops. Evaluation of the activity was carried out using pre-test and post-test knowledge instruments. The results of the activity showed a significant increase in the average midwives' knowledge score from 58.3 (poor category) to 87.5 (good category) after the training (p < 0.001). All participants (100%) were also able to demonstrate DRA screening and guide functional yoga movements correctly and safely. This capacity building is expected to optimize the quality of comprehensive postpartum care at the primary care level.